2015
DOI: 10.2148/benv.41.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of the Recession on British Volume Housebuilders: A Behavioural Analysis

Abstract: The 2008/9 recession had a pronounced impact on the financial performance, stability and output of Britain's volume housebuilders, leading to a historic decline in new housing supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Until 2015, the UK had a mix of policies supporting the lowenergy housing transition (Kern et al, 2017), but key policy objectives were removed in 2015; including the aspiration for zero-carbon new houses and support for the able-to-pay households to undertake energy efficiency improvements (Rosenow and Eyre, 2016). The 2008 financial crisis affected the availability of mortgages (Martin, 2011) and impacted negatively on the construction sector, resulting in a further drop of new built houses (Payne, 2015) that had already been decreasing since 1980 (impacted by, for example, the early 1990s recession and subsequent housing crisis (Gentle et al, 1994). In 2015, 152,440 new houses were built, a 40% reduction compared to 1980 (ONS, 2016).…”
Section: Challenges Of Developing Low-energy Housingmentioning
confidence: 99%
“…Until 2015, the UK had a mix of policies supporting the lowenergy housing transition (Kern et al, 2017), but key policy objectives were removed in 2015; including the aspiration for zero-carbon new houses and support for the able-to-pay households to undertake energy efficiency improvements (Rosenow and Eyre, 2016). The 2008 financial crisis affected the availability of mortgages (Martin, 2011) and impacted negatively on the construction sector, resulting in a further drop of new built houses (Payne, 2015) that had already been decreasing since 1980 (impacted by, for example, the early 1990s recession and subsequent housing crisis (Gentle et al, 1994). In 2015, 152,440 new houses were built, a 40% reduction compared to 1980 (ONS, 2016).…”
Section: Challenges Of Developing Low-energy Housingmentioning
confidence: 99%
“…In its place is usually a neoclassical expectation that a supply response is both inherent to demand side interventions and will yield appropriate housing production. This a priori supply response from demand-side stimuli hides the complexities of actor agency and organisational behaviour that has been shown in recent research to influence housing supply outcomes (Payne, 2015(Payne, , 2013.…”
Section: Understanding Housing Supply Constraintsmentioning
confidence: 85%
“…Their conclusive assumption that this question can only be addressed by models of oligopoly and risk (ibid. ) underplays what more recent research emphasises as the complex organisational decision-making processes that developers adopt in response to market dynamics and policy change Barker, 2018, 2015;Payne, 2015Payne, , 2013.…”
Section: Understanding Housing Supply Constraintsmentioning
confidence: 98%
“…Beyond the technical feasibility issues highlighted by housebuilders as a cause for resisting non-conventional forms of design and construction, the research also revealed that the global financial crisis and recessionary experience (see Payne 2015), together with the ongoing uncertainty in the macroeconomy, skills and materials markets and mortgage finance markets, had further dampened housebuildersÕ strategic, design and technical ambitions around carbon reduction. For housebuilders, this institutional turbulence had amplified the prevailing viability issues associated with delivering policy-compliant product and process innovations.…”
Section: òéI Donõt Have a Problem With Ité By A Simple Calculation I mentioning
confidence: 98%